On Advances of Anonymous Credentials—From Traditional to Post-Quantum - Madusha Chathurangi; Qinyi Li; Ernest Foo (Cryptography)
Anonymous credential (AC) systems are privacy-preserving authentication mech-anisms that allow users to prove that they have valid credentials anonymously. These systems provide a powerful tool for several practical applications, such as anonymous pay-ment systems in e-commerce, preserving robust privacy protection for users. Most existing AC systems are constructed using traditional number-theoretic approaches, making them insecure under quantum attacks. With four decades of research in anonymous credential systems, there is a need for a comprehensive review that identifies the design structures of AC systems, organizes the research trends, and highlights unaddressed gaps for the future development of AC, especially bringing AC to post-quantum cryptography. This work is a complete study describing AC systems, as well as their architecture, components, security, and performance. Additionally, real-world implementations of various applications are identified, analyzed, and compared according to the design structure. Lastly, the challenges hindering the shift toward the quantumly secure lattice-based AC designs are discussed.